Applied models to biodegradation kinetics of lubricant and vegetable oils in wastewater - Montagnolli, Renato N. [UNESP]; Lopes, Paulo R. M. [UNESP]; Bidoia, Ederio Dino [UNESP] (Elsevier B.V., 2009)
Bioremediation technologies are used in order to remove pollutants from the environment in a safe, economical and harmless way during the treatment of waste, especially with the use of techniques such as biodegradation. A lubricant and vegetable oil contaminated water sample was studied in order to evaluate the biodegradability of different types of oils, considering the relevance of the obtained data in the bioremediation procedures. The objective of this paper is to use respirometry technique as a biodegradation process data source, and then apply to the obtained data the experimental design of mathematical models to characterize and determinate how the different types of oils are capable of affecting the parameters in biodegradation kinetics. The kinetics was then evaluated through selected models with a reasonable fit to experimental data. The Bartha and Pramer respirometer is used as a method to accurately measure the CO(2) formation in the organic compounds degradation by microorganisms. Therefore, the difference in biodegradation efficiency process is compared in the different groups of oils using mathematical models fitting the obtained data for the kinetics of biodegradation. The results demonstrated that used lubricant automotive oils are more susceptible to the biodegradation process, since their molecular structures had already been altered after use. In general, automotive lubricant oils shown better performance in biodegradation than vegetable oils. The models proposed for the obtained data in each of these assays demonstrated that vegetable oils biodegradation rate tends to decrease faster and end sooner than the automotive oils. Also, the modeling predicted that higher rates of biodegradation and total CO(2) production are to be expected in automotive lubricant oils rather than vegetable oils. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Biodegradation; Kinetic model; Lubricant oil; Vegetable oil; Respirometry